Decisional conflict among breast cancer patients considering contralateral prophylactic mastectomy. Issue 5 (May 2019) - Manne, Sharon; Smith, Barbara; Mitarotondo, Anna; Frederick, Sara; Toppmeyer, Deborah; Kirstein, Laurie
Highlights: Contralateral prophylactic mastectomy knowledge was low regarding risk-reduction. Preparedness to make the CPM decision were moderate in an average risk sample. Patients were very worried about having another form of breast cancer in the future. CPM was chosen to lower chance of another breast cancer and extend life. Abstract: Objectives: The study's goals were to characterize decisional conflict and preparedness for making the decision about having CPM among breast cancer patients considering CPM who do not carry cancer-predisposing mutation and to evaluate correlates of decisional conflict and preparedness. Methods: 93 women considering CPM completed a survey of decisional conflict and preparedness for the CPM decision, knowledge, perceived risk, self-efficacy, reasons for CPM, input from others and discussion with the doctor about CPM, and cancer worry. Results: Between 8% and 27% of women endorsed elevated decisional conflict. Most women were satisfied with preparatory information that they were provided. Knowledge was low. Top reasons for choosing CPM were the desire for peace of mind, lowering the chance of another breast cancer, and improving survival. Conclusions: Decisional conflict is elevated in a subset of patients considering CPM. A more well-informed decision may be fostered by a comprehensive discussion about CPM with the patient's clinician, fostering self-efficacy in managing cancer worry, and helping patients understand their motivations for CPM. Practice implications: Clinicians working with breast cancer patients considering CPM should discuss the CPM decision, foster self-efficacy in managing cancer worry, and help patients understand their motivations for the surgery.